Development of Augmented Reality-Based and Artificial Intelligence-Assisted E-Modules on Global Warming Materials to Improve Critical Thinking Skills of High School Learners - Dwi Purnomo Aji; Hamdi Akhsan; Leni Marlina (Postgraduate, University of Mataram, 2025)
The background of this research is the low level of critical thinking skills in students and the importance of technology utilization in the learning process. To deal with students' low critical thinking skills can be done by utilizing technology in the packaging of teaching materials in the form of e-modules based on Augmented Reality and Artificial Intelligence Assisted on Global Warming Material. This development procedure uses the Akker model in three stages: analysis, design, and evaluation, with 179 students involved. The findings of this study indicate that the products made have reached the valid category with an average value of the electronic validity of the module from the five aspects of 94.3%. Then, the final average of the results of student responses to the use of e-modules on global warming material amounted to 3.45 with a convenient product category. From the results of the N-Gain test using SPSS version 22.0, the results obtained are for the N gain value of 0.71 ≥ 0.70. So, it can be said that using electronic modules based on Augmented Reality and Artificial Intelligence on global warming material at SMA Negeri 3 Sekayu is adequate to improve students' critical thinking skills.